Analysis of force vector field during centrifugation for optimizing cell sheet adhesion. (17th June 2019) - Haraguchi, Yuji; Kagawa, Yuki; Kubo, Hirotsugu; Shimizu, Tatsuya
Abstract: A three‐dimensional tissue was fabricated by layering cell sheets with centrifugation. In this system, an optimal centrifugal force promoted the adhesion between (a) a cell sheet and a culture dish, and (b) layered cell sheets, resulting in a significant decrease in the fabrication time of the tissue. However, negative effects like sliding/significant deformation of cell sheets were observed upon high rotational speed use. These negative effects inhibit the further shortening of the fabrication time. The sliding/deformation suggests that the centrifugal forces were applied on the cell sheets in unwanted directions. Studies on the force vector field applied to the object placed on the plate during centrifugation are not available, and thus, the reason for the occurrence of such negative effects is unclear. Here, we theoretically derived the spatial distribution of acceleration applied on a plate during centrifugation. Using this theory, we found that the negative effects were triggered by the centrifugal force in the direction parallel to the plate surface, which appeared due to an inclination of the plate surface against a horizontal plane. Therefore, by adding weights on the plate edge to maintain the plate surface in a horizontal position, we succeeded in eliminating the negative effects and in increasing the rotational speed, with the minimum risk of sliding/deformation of cell sheets. We succeeded in reducing the time to establish tight adhesion between a mouse myoblast sheet and a culture dish, and layered cell sheets by increasing the centrifugal force from 5 min to 1 min without significant cytotoxicity.